2001
DOI: 10.1148/radiol.2211010086
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychologic Correlates of Brain White Matter Lesions Depicted on MR Images: 1921 Aberdeen Birth Cohort

Abstract: Lower fluid-type ("prevailing") intelligence test scores were associated with increased severity of white matter lesion ratings but not crystallized-type ("premorbid") intelligence test scores. This indicates that MR imaging-depicted white matter lesions are of clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 32 publications
3
52
0
2
Order By: Relevance
“…Since cognitive effort normally triggers an increase in cerebral blood supply in response to increasing metabolic demands, any reduction in vascular reactivity is likely to induce a decline in mental efficiency. The greatly increased incidence of white matter lesions in adults with hypertension [52,53] could also underlie the decline in mental efficiency, since the presence of white matter lesions is associated with slower performance on psychomotor tasks like the DSST [54,55]. Whether those declines reflect neural changes secondary to demyelination [56] or to the haemodynamic abnormalities associated with white matter lesions [57] remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Since cognitive effort normally triggers an increase in cerebral blood supply in response to increasing metabolic demands, any reduction in vascular reactivity is likely to induce a decline in mental efficiency. The greatly increased incidence of white matter lesions in adults with hypertension [52,53] could also underlie the decline in mental efficiency, since the presence of white matter lesions is associated with slower performance on psychomotor tasks like the DSST [54,55]. Whether those declines reflect neural changes secondary to demyelination [56] or to the haemodynamic abnormalities associated with white matter lesions [57] remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…The present article examines the association between brain white matter abnormalities (WML and PVL) and cognitive change measured across most of the human life span (age 11 to age 78 years). It is based on the same cohort sample as the report by Leaper et al (2001): (a) It adds a few new participants; (b) it analyzes a different combination of psychometric tests; (c) it presents entirely new analyses; and (d) it introduces the effect of medical conditions, especially hypertension. Both PVL and deep WML are rated separately.…”
Section: Prior Mental Abilitymentioning
confidence: 99%
“…Childhood intelligence is the strongest predictor of late-life intelligence and accounts for about 40% of the variance in intelligence at age 78 . Magnetic resonance imaging (MRI)-detected white matter hyperintensities (WMH) (Young et al 2008) are associated with vascular risk factors (Murray et al 2005) and with reduced cognitive ability and dementia in older adults (Leaper et al 2001;Firbank et al 2007). We previously found that WMH contribute 14% of the variance in cognitive ability at age 78, that WMH are linked to hypertension , and it is now widely accepted that WMH are an imaging biomarker of vascular disease (Kearney-Schwartz et al 2009, Raz et al 2007, Fischer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional investigations into the relationship between hypertension, WMH and late-life cognition are limited by difficulty in controlling for prior cognitive ability (Leaper et al 2001, Wright et al 2008, Breteler et al 1994. While longitudinal population-based studies confirm the negative effect of WMH on cognitive ageing (Silbert et al 2008, Gouw et al 2008, it is unclear whether WMH in late midlife, are as detrimental to the lifelong cognitive trajectory as in the eighth decade.…”
Section: Introductionmentioning
confidence: 99%